Autophagy in doxorubicin resistance: basic concepts, therapeutic perspectives and clinical translation - Zhang, Yantao; Ji, Yanqin; Tu, Yanyang; Li, Yi (Frontiers in Immunology, 2025)
Doxorubicin (DOX) is still one of the leading compounds for cancer chemotherapy, but its clinical application has been restricted by the drug resistance. The emerging evidence has demonstrated that autophagy is a meticulously regulated by the lysosomal degradation as a regulator of this drug resistance. Autophagy can exert a pro-survival strategy under therapeutic stress through recycling cellular components, inhibiting apoptosis and remodelling metabolism, thereby enhancing carcinogenesis. The present review aims to highlight the interaction between autophagy and DOX resistance, providing the molecular machinery of autophagy and its control by genetic factors, microenvironmental factors and non-coding RNAs. Mechanistically, autophagy can be considered as protective or cytotoxic, relying on the cellular context, but in most cases, autophagy serves as a survival pathway promoting chemoresistance. The present review will also discuss about the function of DOX in autophagy induction through ROS generation, DNA damage response and AMPK/mTOR axis, whereas providing context-specific adaptations including mitophagy in cancer stem cells and lysosomal remodelling. The pre-clinical studies have highlighted the function of pharmacological compounds and nanoparticles for the regulation of autophagy for improving DOX sensitivity in cancer, accelerating therapeutic index. The strategies have focused on the application of small-molecule inhibitors, natural compounds, nanocarrier-mediated co-delivery of DOX with autophagy modulators and the development of combination therapeites providing the crosstalk of autophagy and cell death mechanisms in DOX resistance. The clinical translation depends on the development of more effective autophagy-targeted drugs in combination therapies. Hence, the present review highlights the role of autophagy as a biomarker and therapeutic factors in reversing DOX resistance. By elucidating the complex biology linking autophagy to drug resistance, it is emphasized that tailored approaches integrating autophagy modulation may yield more effective and less toxic cancer treatments.